The Factors Influencing Trade in Services - an Outlook for the Business Services Industry in Poland - Chilimoniuk-Przeździecka, Eliza; Kuźnar , Andżelika (Studia Oeconomica Posnaniensia, 2026)
In recent years, both in the world and in Poland, the export of enterprises providing services related to business services is dynamically growing. Empirical studies of factors, which determinate the volume of service exports, are under- developed due to the incompleteness of bilateral trade statistics. New data sources fill the gap in the literature. The purpose of this paper is to identify the factors influencing the export of services. The assessment is made with the gravity model. Due to the availability of data, the empirical study covers the years 2000-2010. Information on bilateral trade flows comes from the Trade in Services Database (TSD). In this analysis we focus on the exports of services from one country, i.e. the US to the EU-27 and the rest of the 36 countries in the world for which data is available. In addition to variables commonly used in such models, this one also includes variables related to intellectual property protection. Identifying the determinants of trade in services is an introduction to the recommendation for Poland on which of the factors affecting exports the attention should be focused on and their development should be shaped to ensure long-term and stable growth of the business services sector in Poland based on exports